Google Cloud Platform administration : design highly available, scalable, and secure cloud solutions on GCP - Thakurratan, Ranjit Singh (Packt Publishing, 2018)
Make the most of GCP's offerings to manage your data center workload and optimize deployments Key Features Discover new techniques to administer, manage, and deploy applications on GCP Understand effective solutions for storing, retrieving, and deploying your container images Explore various offerings of GCP for operations and security Book Description On-premise data centers are costly to manage. If you need a data center but don't want to deal with a physical one, Google Cloud Platform (GCP) is the solution. With GCP, you can build, test, and deploy applications on Google's infrastructure. Google Cloud Platform Administration begins with GCP fundamentals, with the help of which you will deploy your first app and gain an understanding of Google Cloud architecture and services. Furthermore, you will learn how to manage Compute, networking, and storage resources. As you make your way through the book, you will learn how to track and manage GCP's usage, monitoring, and billing access control. You will also be able to manage your GCP's access and permissions. In the concluding chapters, you will explore a list of different developer tools for managing and interacting with the GCP platform. By the end of this book, you will have learned how to effectively deploy workloads on GCP. What you will learn Understand all GCP Compute components Deploy and manage multiple GCP storage options Manage and utilize the networking resources offered by GCP Explore the functionalities and features of the GCP Container Understand the workings of GCP operations such as monitoring and error reporting Discover an immune GCP using its identity and security options Who this book is for Google Cloud Platform Administration is for administrators, cloud architects, and engineers who want to leverage the upcoming Google Cloud Platform. Some basic understanding of cloud computing will be useful.